Contrasting long-term dynamics of antimicrobial resistance and virulence plasmids in Salmonella Typhimurium from animals. Issue 8 (23rd August 2022) - Mellor, Kate C.; Blackwell, Grace A.; Cawthraw, Shaun A.; Mensah, Nana E.; Reid, Stuart W. J.; Thomson, Nicholas R.; Petrovska, Liljana; Mather, Alison E.
Abstract : Plasmids are mobile elements that can carry genes encoding traits of clinical concern, including antimicrobial resistance (AMR) and virulence. Population-level studies of Enterobacterales, including Escherichia coli, Shigella and Klebsiella, indicate that plasmids are important drivers of lineage expansions and dissemination of AMR genes. Salmonella Typhimurium is the second most common cause of salmonellosis in humans and livestock in the UK and Europe. The long-term dynamics of plasmids between S . Typhimurium were investigated using isolates collected through national surveillance of animals in England and Wales over a 25-year period. The population structure of S . Typhimurium and its virulence plasmid (where present) were inferred through phylogenetic analyses using whole-genome sequence data for 496 isolates. Antimicrobial resistance genes and plasmid markers were detected in silico . Phenotypic plasmid characterization, using the Kado and Liu method, was used to confirm the number and size of plasmids. The differences in AMR and plasmids between clades were striking, with livestock clades more likely to carry one or more AMR plasmid and be multi-drug-resistant compared to clades associated with wildlife and companion animals. Multiple small non-AMR plasmids were distributed across clades. However, all hybrid AMR–virulence plasmids and most AMR plasmids were highly clade-associated and persisted over decades, with minimal evidence of horizontal transfer between clades. This contrasts with the role of plasmids in the short-term dissemination of AMR between diverse strains in other Enterobacterales in high-antimicrobial-use settings, with implications for predicting plasmid dissemination amongst S . Typhimurium.